La parole de l’enfant victime de crimes sexuels dans les procédures judiciaires aux Assises de la Charente (1889-1914) - Marie Rougier (Criminocorpus)
In a context of a child welfare emerging from the end of the 19th century and paradoxically the development of theses supported by forensics on the mythomania of children in cases of indecent assault, this article proposes to question the place given to the speech of the child victim of a sexual crime with his depositories, and then throughout the investigation process.To achieve this objective, this study is based on the systematic counting of 68 procedural files of cases of rape, indecent assault and incest committed on minors and judged by the Court of Assizes of Charente, courts of Angoulême, Cognac, Barbezieux and Confolens from 1889 to 1914 and the exploitation of the charges, police or gendarmerie minutes, interrogations of investigating judges, hearing witnesses and medicals expertises.